(untitled) (East West Medical College Journal, 2026)
Background: Modified Radical Mastectomy (MRM) is traditionally performed under general anesthesia. Thoracic segmental spinal anesthesia (TSSA) has emerged as an alternative that targets thoracic sensory segments, potentially offering stable hemodynamics, superior postoperative analgesia, and reduced opioid use. Objective: To synthesize contemporary evidence (2022–2025) on the efficacy, safety, and practical technique of TSSA for MRM, and to present a composite summary of outcomes from recent case series and randomized trials. Methodology: We performed a narrative synthesis of randomized trials, prospective observational studies, case series and reviews published from 2022–2025. Key outcomes extracted included adequacy of surgical anesthesia, conversion rates to general anesthesia, hemodynamic stability, respiratory complications, postoperative analgesia duration, and patient/provider satisfaction. Results: Across randomized trials and observational series, TSSA reliably provided adequate surgical anesthesia for MRM with low conversion rates. Compared with general anesthesia, TSSA was associated with superior early postoperative analgesia, reduced intraoperative and postoperative opioid requirements, high patient satisfaction, and acceptable hemodynamic stability. Reported complications were infrequent and generally minor (transient hypotension, nausea, need for light sedation); serious respiratory or neurological complications were rare in published series when proper patient selection and technique were used. Conclusion: TSSA is a feasible and effective regional anesthetic technique for MRM in selected patients and centers experienced with thoracic neuraxial blockade. Further multicenter randomized trials with standardized protocols are recommended to define best practice and long-term outcomes. EWMCJ Vol. 14, No. 2, July 2026: 230-233